2009
DOI: 10.1074/jbc.m807311200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Plant Plasma Membrane H+-ATPase by 14-3-3 Proteins Is Negatively Controlled by Two Phosphorylation Sites within the H+-ATPase C-terminal Region

Abstract: The proton pump ATPase (H ؉ -ATPase) of the plant plasma membrane is regulated by an autoinhibitory C-terminal domain, which can be displaced by phosphorylation of the penultimate Thr residue and the subsequent binding of 14-3-3 proteins. We performed a mass spectrometric analysis of PMA2 (plasma membrane H ؉ -ATPase isoform 2) isolated from Nicotiana tabacum suspension cells and identified two new phosphorylated residues in the enzyme 14-3-3 protein binding site: Thr 931 and Ser 938 . When PMA2 was expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 42 publications
(49 reference statements)
2
36
0
Order By: Relevance
“…Western blotting of the purified PMA2 isoforms (Fig. 6) showed that PMA2-Ser938Asp had a lower level of phosphorylated Thr-955 and less bound 14-3-3 proteins than the wild type, as described previously (14). When compared with unmodified PMA2, the mutation of Thr-889 into alanine or aspartate did not modify FIGURE 5.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Western blotting of the purified PMA2 isoforms (Fig. 6) showed that PMA2-Ser938Asp had a lower level of phosphorylated Thr-955 and less bound 14-3-3 proteins than the wild type, as described previously (14). When compared with unmodified PMA2, the mutation of Thr-889 into alanine or aspartate did not modify FIGURE 5.…”
Section: Resultsmentioning
confidence: 98%
“…However, whether 14-3-3 protein binding was required remains unanswered. Recently, it was shown that the PMA2-Ser938Asp (PMA2-S938D) mutation prevents 14-3-3 protein binding and fails to sustain yeast growth and that, in this mutant, Thr-955 phosphorylation is decreased, but not abolished (14). If we hypothesize that activation of H ϩ -ATPase by phosphorylation of Thr-889 requires Thr-955 phosphorylation, but not the binding of 14-3-3 proteins, the double mutant PMA2-Thr889Asp-Ser938Asp (PMA2-T889D-S938D) should be devoid of bound 14-3-3 proteins but still sustain yeast growth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations